2015
DOI: 10.1037/xhp0000033
|View full text |Cite
|
Sign up to set email alerts
|

Older and younger adults’ strategies in sensorimotor tasks: Insights from Fitts’ pointing task.

Abstract: We investigated how young and older adults differ in sensorimotor tasks. Two groups of participants (young and older adults) performed discrete Fitts' tasks in which 4 levels of difficulty (ID) were used, resulting from either the manipulation of the size of the target (ID(W)) or of the distance between home and target positions (ID(D)). Kinematic analysis allowed distinguishing 4 different types of strategies used to reach the target, on the basis of the existence and the nature of submovements. Results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 56 publications
5
32
1
Order By: Relevance
“…Based on this methodology, we showed that these kinematic patterns fulfill the currently accepted criteria to empirically distinguish among strategies, namely: (a) main effect of strategies on collected measures (e.g., performance); (b) interaction effects between the strategy factor and one or several factors on strategy use and strategy performance; and (c) age-related differences in strategy use and performance (see Poletti et al, 2015). We empirically documented the usefulness of a strategy approach to further our understanding of processes underlying age-related changes in sensorimotor performance.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Based on this methodology, we showed that these kinematic patterns fulfill the currently accepted criteria to empirically distinguish among strategies, namely: (a) main effect of strategies on collected measures (e.g., performance); (b) interaction effects between the strategy factor and one or several factors on strategy use and strategy performance; and (c) age-related differences in strategy use and performance (see Poletti et al, 2015). We empirically documented the usefulness of a strategy approach to further our understanding of processes underlying age-related changes in sensorimotor performance.…”
Section: Introductionmentioning
confidence: 84%
“…Recently, we have undertaken to extend this framework to the sensorimotor domain using the Fitts’ rapid-aiming task (Poletti et al, 2015, 2016). We made this choice since control processes used during aiming movement in Fitts’ task are representative of those used in several motor tasks (e.g., Abbs et al, 1984; Duysens and Van de Crommert, 1998; Collins and De Luca, 1993; Van de Crommert et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Although FL has been shown to hold well for all ages, 3,4 age-related differences has been reported. Despite grown-ups of different age did not differ whether ID was manipulated through amplitude or width, 5 children and older people do seem to show higher slopes of the regression lines (ID x MT) when compared to young adults. 6,7 Children and elderly therefore appear to be more sensitive to changes in ID and this age-related sensitivity is one clue to believe that individual differences might influence SATO.…”
Section: Methodsmentioning
confidence: 99%
“…5 The combination of these age-related strategies with personality traits calls for further investigation.…”
Section: Discussionmentioning
confidence: 99%